(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The global green economy represents a significant transition towards sustainable and environmentally friendly practices that harmonize economic development with the safeguarding of the environment. This comprehensive study examines renewable energy, sustainable agriculture, green technologies, and environmental regulatory frameworks within the context of the green economy. This article analyzes case studies, economic data, and policy outcomes to elucidate the advantages and disadvantages of implementing environmentally friendly practices in the economy. The data demonstrates the positive impact of investing in the green industry, which includes reducing climate change, generating employment opportunities, fostering innovation, and advancing social equity. The report also analyzes the geopolitical and economic impacts of the green transition, uncovering the worldwide collaboration required to achieve sustainable development objectives. This paper asserts that the promotion of the global green economy and the guarantee of a sustainable and prosperous future require the implementation of coordinated policies and robust international collaboration.